2020
DOI: 10.1007/s11626-020-00518-6
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of miRNA-23a-3p rescues high glucose-induced cell apoptosis and proliferation inhibition in cardiomyocytes

Abstract: Maternal hyperglycemia potentially inhibits the development of the fetal heart by suppressing cardiomyocyte proliferation and promoting apoptosis. Different studies have indicated that miRNAs are key regulators of cardiomyocyte proliferation, differentiation, and apoptosis and play a protective role in a variety of cardiovascular diseases. However, the biological function of miRNA-23a in hyperglycemia-related cardiomyocyte injury is not fully understood. The present study investigated the effect of miRNA-23a-3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…In the present study, results from bioinformatics prediction indicated that miRNA-23a was an upstream miRNA regulating VEGF, with similar and highly conservative sequences within the targeted regions in human and rat models. miRNA-23a is widely involved in the regulation of various physiological and pathological processes in the body, which plays an important role in the cellular differentiation (45)(46)(47). miRNA-23a has been shown to be involved in the formation of skeletal muscle, hematopoietic cell differentiation and bone metabolism (48).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, results from bioinformatics prediction indicated that miRNA-23a was an upstream miRNA regulating VEGF, with similar and highly conservative sequences within the targeted regions in human and rat models. miRNA-23a is widely involved in the regulation of various physiological and pathological processes in the body, which plays an important role in the cellular differentiation (45)(46)(47). miRNA-23a has been shown to be involved in the formation of skeletal muscle, hematopoietic cell differentiation and bone metabolism (48).…”
Section: Discussionmentioning
confidence: 99%
“…Many researchers have focused on how to prevent or reduce myocardial injury. Many studies have found that cell‐derived exosomes can carry and transfer myocardial protective miRNAs into damaged cardiomyocytes and have the beneficial effect of cardiac protection 11,12 . They play a critical role in the myocardial injury repair process, but the specific regulatory mechanism of miRNAs in AMI remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Cell proliferation was analyzed via EdU assay by kFluor555 Click-iT EDU Kit (KeyGen) [ 20 ]. 4 × 10 4 cells were plated in the 96-well plates overnight and cell transfection was performed for 48 h, followed by cell labeling with EDU working solution.…”
Section: Methodsmentioning
confidence: 99%